Building Urban Government in Ho Chi Minh City, Viet Nam - HIEN, Dr. BUI NGOC (The journal of contemporary issues in business and government, 2021)
In the process of international integration, Vietnam's socio-economy has achieved great achievements. The urbanization process in Vietnam is happening on a large scale and at a fast pace, so the construction of urban government is an indispensable requirement. Therefore, the roadmap and implementation method must be studied seriously and comprehensively in order to build an appropriate urban government model, meeting the new requirements set out in terms of efficiency improvement and state management in the current context. Ho Chi Minh City is a special city, a major center of economy, culture, education - training, science - technology, a focal point for international exchange and integration. attracting and spreading to the southern key economic region, having an important political position of the whole country. In order to create a driving force for Ho Chi Minh City's development, in recent years, the city has developed an urban government, contributing to improving the effectiveness and efficiency of State management, promoting administrative reform, improving the investment environment contributes to the development of society. However, the construction of urban government in Ho Chi Minh City today has limitations. The article outlines the urgency, characteristics and issues raised in the construction of urban government in Ho Chi Minh City.